Influence of non-ventilating intervals during early incubation stage on egg hatching process - Wesam A. Fares; Mona R. M. Ahmed; R. E. Rizk; E. H. A. Shahein; N. G. Boutrous; Karim El-Sabrout (Veterinary World, 2023)
Background and Aim: The exchange of oxygen and carbon dioxide (CO2) in the incubator plays a key role in embryonic development and hatching. This study aimed to study the effect of non-ventilated (NV) intervals during the early stage of embryonic development on the hatching process.